Genotoxic effect and vitellogenin gene expression in Oreochromisniloticus on exposure to endocrine disruptor chemicals (EDC) / Aisyah binti Abdul Hamid - Abdul Hamid, Aisyah (2014)
This study was conducted to evaluate the genotoxicity of atrazine and endosulfan as a potential endocrine disruptor chemicals (EDCs) in Oreochromis niloticus by using micronucleus test and RAPD assays, as well as to determine vitellogenin gene expression in male O. niloticusfor 96 hours exposure period. O. niloticus was exposed to atrazine at concentration of 0.50 mg/L, 2.50 mg/L, and 4.75 mg/L, and to endosulfan concentration of 1.50 μg/L, 3.60 μg/L, and 7.00 μg/L. In the micronucleus test, athigh concentration of atrazine and endosulfan, there was a significant increase of the frequency of micronucleus and nuclear abnormalites. These results showed that exposure to atrazine and endosulfan significantly increased genetic toxicity in O. niloticus blood cells. A subsequent RAPD assay also showed that atrazine and endosulfan induced genotoxic effect in O. niloticusby changing the DNA profiling as compared to control test. The five RAPD primers tested produced unique polymorphic band patterns and generated RAPD profile variations that displayed the disappearance of bands and appearance of new bands of amplified DNA in the atrazine and endosulfan-treated genomic DNA. There was also induction of vitellogenin transcript observed in male O. niloticus upon treatment to all atrazine concentrations and high concentrations of endosulfan. These results suggested that atrazine and endosulfan are potentially harmful to fishes as EDCs as the chemicals have been shown to cause genotoxicity effect and vitellogenin expression in male O. niloticus.